Effectiveness of manual therapy applied to craniomandibular structures in temporomandibular disorders: A systematic review. (17th January 2022) - Asquini, Giacomo; Pitance, Laurent; Michelotti, Ambra; Falla, Deborah
Abstract: Background: Within physical therapy, manual therapy is known to be effective for managing temporomandibular disorders (TMDs). However, manual therapy is a broad term including different approaches applied to different body regions. Aims: This is the first systematic review that aims to evaluate the effectiveness of manual therapy applied specifically to the craniomandibular structures (Cranio‐Mandibular Manual Therapy [CMMT]) on pain and maximum mouth opening in people with TMD. Material and methods: This systematic review was developed based on a pre‐determined published protocol which was prospectively registered with PROSPERO (CRD42019160213). A search of MEDLINE, Embase, CINAHL, ZETOC, Web of Science, SCOPUS, PEDro, PubMed, Cochrane Library and Best Evidence, EBM reviews–Cochrane Central Register of Controlled Trials, Index to Chiropractic Literature ChiroAccess and Google Scholar databases was conducted from inception until October 2020. Randomised controlled trials comparing the effect of CMMT on pain and maximum mouth opening versus other types of treatment in TMDs were included. Two reviewers independently screened articles for inclusion, extracted data, assessed risk of bias with the revised Cochrane risk of bias tool for randomised trials and evaluated the overall quality of evidence with the Grading of Recommendations, Assessment, Development and Evaluations. Results: A total of 2720 records were screened, of which only 6 (293 participants) satisfied the inclusion criteria. All studies showed some concerns in risk of bias, except for one, which was high risk of bias. The overall quality of evidence was very low for all outcomes because of high heterogeneity and small sample sizes. All studies showed a significant improvement in pain and maximum mouth opening for CMMT from baseline in the mid‐term, but only two showed superiority compared to other interventions. Given the high heterogeneity and small sample sizes of the included studies, a quantitative synthesis was not performed. Discussion and conclusion: There is the need for future high methodology research investigating different manual therapy techniques applied to different regions and different populations (e.g., chronic versus acute TMD) to determine what is most effective for pain and maximum mouth opening in patients with TMDs.